APPLICABILITY OF DRY MILK DRINKS IN THE NUTRITION OF CHILDREN AFTER ONE YEAR - N. G. Zvonkova; Т. E. Borovik; N. N. Semenova; Т. V. Bushueva; I. М. Guseva; V. А. Skvortsova; Т. N. Stepanova; S. V. Nekrasova ("Paediatrician" Publishers LLC, 2014)
The data on the value of milk and dairy products in the nutrition of children aged from 1 to 3 years are provided. In the Russian consumer market for children of this age there are new products on the basis of cow and goat milk, so-called third formulas, which have the balanced structure, contain optimum amount of vitamins, mineral substances, enriched with pre- and probiotics, long chain polyunsaturated fatty acids, nucleotides and are functional food products. The results of randomized researches testifying to positive influence of «the third formulas» on a state of health of children, their provision with vitamins and mineral substances are presented.